KASL clinical practice guidelines: Management of nonalcoholic fatty liver disease - Kang, Seong Hee; Lee, Hye Won; Yoo, Jeong-Ju; Cho, Yuri; Kim, Seung Up; Lee, Tae Hee; Jang, Byoung Kuk; Kim, Sang Gyune; Ahn, Sang Bong; Kim, Haeryoung; Jun, Dae Won; Choi, Joon-Il; et al. (Clinical and molecular hepatology, 2021)
[...]the clinical practice guidelines committee began revising the guidelines to reflect the results of Korean and international research and develop new recommendations based on a systematic approach that reflects evidencebased medicine and expert opinions. Intended users The aim of these guidelines is to provide useful clinical information and direction to healthcare providers involved in the diagnosis and treatment of NAFLD patients. [...]these guidelines are intended to provide definite and practical information to resident physicians, practitioners, and trainers. According to the types of studies, randomized, controlled studies were approached from a high level of evidence, while observational studies were approached from a low level of evidence. The significant safe limits of daily alcohol intake that distinguish NAFLD from alcoholic fatty liver disease range from 10–40 g (pure alcohol), though that range varies between studies. [...]definite criteria are difficult to recommend.